America's game: The NFL's "Salute to Service" campaign, the diffused military presence, and corporate social responsibility. (2nd January 2016) - Rugg, Adam
ABSTRACT: This article critiques the National Football League's (NFL) "Salute to Service" campaign that highlights and celebrates the US military. As the campaign produces a saturation of military symbolism and iconography in and around regular season games, the campaign turns away from the unique "mega-event" model of military ceremonial display and toward a "diffused military presence" that casually incorporates the military into everyday life via the entertainment and branding structures of the league. It further constructs the league as not just a compassionate corporate citizen passively embodying "American values, " but as an ideologically active and authoritative American public institution.